Neural and Synaptic Defects in Autism Spectrum Disorders - Hansen Wang (Frontiers Research Topics, 2015)
Autism spectrum disorders (ASDs) are a group of genetically and clinically heterogeneous neurodevelopmental disorders characterized by impaired reciprocal social interactions and communication, and restricted and repetitive patterns of behaviors and interests. Studies in genetics, neurobiology and systems biology are providing insights into the pathogenesis of ASDs. Investigation of neural and synaptic defects in ASDs not only sheds light on the molecular and cellular mechanisms that govern the function of the central nervous system, but may lead to the discovery of potential therapeutic targets for autism and other cognitive disorders. Our Research Topic which constitutes this e-book documents the recent development and ideas in the study of pathogenesis and treatment of ASDs, with an emphasis on syndromic disorders such as fragile X and Rett syndromes. In addition, model systems and methodological approaches with translational relevance to autism are covered herein. We hope that the Research Topic will enhance the global knowledge base in the autism research community and foster new research directions in autism related biology.